ANEMIA AS RISK FACTOR OF HANDGRIP STRENGTH DECREASED ON ELDERLY IN YOGYAKARTA PROVINCE’S PANTI WERDHA - Ganda Hidayat; Johan Kurnianda; I Dewa Putu Pramantara (Acta Interna The Journal of Internal Medicine, 2011)
Background: According to the WHO, by the end of 20 th century, the more the world population grow, the more the elderly population will be. Yogyakarta province has a 13.72% of Indonesian elderly. The anemia prevalence increased as the age added. Aging process resulted in strength muscle reduced. Handgrip strength test is a valid and consistent as well as simple alternative to value the muscle strength decreased advanced age. Purpose of this study is to know whether anemia is a risk factor against muscle strength decreased measured by handgrip strength test on elderly population in nursing house. Method: This study used cross sectional study design. The study time was in August 2010. The advance ages fullfilling the inclusion and exclusion criteria followed physical examination, routine blood test and handgrip strength measurement. Result: This study involved 118 elderly participants. There was difference of mean handgrip strenght in: age (14.52 kg vs 19.64 kg; p=0.001), gender (13.39 kg vs 22.47 kg; p=0.001), activity level (7.94 kg vs 16.75 kg; p=0.001) and anemia status (13.60 kg vs 17.84 kg; p=0.001); for women even in mild anemia group, there was difference with non anemia group (12.36 kg vs 14.68 kg ; p=0.027). Conclusion: According to multivariable analysis,. There are 3 factors affecting handgrip strength in elderly, namely; Age, activity levels, and anemia which are statistically significant. In this study, it was concluded that anemia is a risk factor of handgrip strength decreased in elderly, for women even in mild anemia, there was statistically significant different with non anemia group. Keywords : Elderly, anemia, handgrip strength